Seismic experiment at the Strokkur Geyser, Iceland, allows to derive a catalogue of over 70,000 eruptions - Eibl, Eva P. S; Jousset, Philippe; Dahm, Torsten; Walter, Thomas R.; Hersir, Gylﬁ Pall; Vesely, Nele I. K. (GFZ Data Services, 2019)
Abstract Geysers are accessible sites of hot pots, springs and pools that regularly erupt. To investigate the frequency and dynamics of water eruptions we setup a local broadband seismic network at Strokkur geyser, Iceland. The experiment was running for 1 year, from June 2017 to June 2018. Four broadband seismic stations (Nanometrics Trillium Compact Posthole 20s) were buried 30-40 cm deep in the ground at a distance of 39 m (G4, SE), 47 m (G3, SW), 43m (G2, N) and 96 m (G1, NE) from the center of the Strokkur pool geyser. Regular visits and 2-month interval battery replacement allowed to power the stations without solar panels, therewith limiting visibility and site impact. From this data we picked a catalog of 73,466 eruptions, that are statistically further evaluated in Eibl et al. (2020), allowing to distinguish 50,135 single eruptions, and over 20,000 multiplet eruptions (i.e. several eruptions in close succession). The mean waiting time after an eruption at Strokkur linearly increased from 3.7 to 16.4 min for single and multiplets, respectively. This data publications releases the catalog of 73,466 eruptions.